OS6.4 The hypoxia-induced glioma derived exosome miRNA-199a-3p promotes glioma cells proliferation and increased ischemic injury of the para-tumor neurons by inhibiting mTOR pathway— A pivotal ischemic mechanism in the proliferation and growth of glioma. (6th September 2019) - Zhao, J; Hu, J; Xie, R
Abstract: BACKGROUND: Growth of glioma cells can be promoted by hypoxia, but its underlying molecular mechanisms are not clear. Exosomes and miRNAs were reported to play crucial roles in tumor progression. Effects of exosomes and exosomal miRNAs, induced by hypoxia, on glioma cells were still unclear. MATERIAL AND METHODS: Glioma samples were analyzed by HE and HIF-1α staining. Image data of these patients were also retrospectively analyzed. HT22 and C6 cell lines were co-cultured in both direct and indirect system. Hypoxia (1% oxygen) and oxygen and glucose deprivation (OGD) were applied to evaluate hypoxia effects on the growth and proliferation of cell lines, and such effects were assessed by C6/HT22 ratio, MTT and LDH assay. Hypoxia-induced glioma derived exosomes (HIGDE) and non-HIGDE (NHIGDE) were isolated and were administrated to normal culture medium to evaluate their effects on cell growing. The target miRNA was selected by performing miRNA microarray analysis. MicroRNA mimics and shRNA were constructed to overexpress or inhibit the microRNA expression. MTOR signal pathway was activated by utilizing phosphatidic acid. The RNAs expression were detected by RT-qPCR and the proteins expression was evaluated by western blotting. RESULTS: Para-tumor hypoxia area shared a same region with cytotoxic edema around the glioma lesion and can be easily detected by PET/CT. The density of positive HIF-1αstaining was higher in tumor area than that in para-tumor and normal parenchyma area. In hypoxia direct co-culture system, the cell number ratio of C6/HT22 was significantly higher than that without hypoxia pretreatment; while in hypoxia mono-culture and indirect co-culture systems, the proliferation ability of HT22 was statistical lower than C6. After applying OGD, neuron cells cultured with HIGDE showed a statistical higher LDH release level than with NHIGDE or normal culture medium. The miRNA microarray analysis revealed that miRNA-199a-3p was the highest expressed in HIGDE than in NHIGDE (p < 0.05; Fold Change > 2). Transfected with mimics or shRNA, it was indicated that upregulation of miR-199a-3p aggravated HIGDE-induced OGD injury in HT22 cells. Moreover, we interfered mTOR signal pathway and the expression of HIF-1αin C6 cells. We found that miRNA-199a-3p aggravated HIGDE-neuron cell injury via suppressing mTOR signal pathway, and hypoxia related upregulation of miRNA-199a-3p in HIGDE was induced by the activation of HIF-1α in C6 cells. CONCLUSION: The Hypoxia-Induced Glioma Derived Exosome miRNA-199a-3p can be upregulated by the activation of HIF-1α, and is able to promote glioma cells proliferation and increase ischemic injury of the para-tumor neurons via inhibiting mTOR pathway.